Relationship between Dosage Accuracy and the Success of Dengue Fever Therapy in Children - Nabila Adiesty Putri Latifiana; Truly Anggraini; Hartono Hartono (Indonesian Journal of Global Health Research, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease transmitted through the bite of the Aedes aegypti mosquito. In 2024, DHF cases in Indonesia reached 1,010 cases, most of which occurred in children, with a mortality rate of 34 cases. DHF therapy generally uses electrolyte fluids and antipyretics. Accurate dosage is crucial for achieving successful therapy and maintaining normal temperature and hematocrit. This study aims to determine patient characteristics, the accuracy of antipyretic and fluid therapy dosages, and the relationship between the accuracy of antipyretic drug dosages and fluid therapy with therapeutic success in pediatric DHF patients at the Inpatient Unit of DKT Slamet Riyadi Hospital, Surakarta. This study is non-experimental with a cross-sectional observational approach. Data were collected and analyzed by reviewing the medical records of DHF patients during the 2021-2023 period, resulting in a total sample of 30 pediatric patients. The data collected was then processed to analyze drug therapy given to pediatric DHF patients, with a focus on evaluating drug rationality based on appropriate dosage categories. The results of the analysis are presented in a table to show the percentage of dengue fever medication use in pediatric patients at DKT Slamet Riyadi Surakarta Hospital, along with relevant analysis. The results show that all patients (100%) were aged 1-5 years, with 56.67% male and 43.33% female. The accuracy of antipyretic (paracetamol) and fluid therapy (RL) dosages was 86.66% accurate. The Chi-Square statistical test showed a p-value (<0.05), indicating a relationship between dosage accuracy and the success of dengue fever therapy in pediatric patients.